Treating and triggering hyperinflammation: tackling hemophagocytic lymphohistiocytosis and HLH-like syndromes in the pediatric cell therapy and critical care setting - Wobma, Holly; Henderson, Lauren A.; Duncan, Christine N.; Prockop, Susan E.; Randolph, Adrienne G.; Degar, Barbara A.; Lehmann, Leslie E.; Baumeister, Susanne H. C. (Frontiers in Oncology, 2025)
Hemophagocytic lymphohistiocytosis (HLH) describes a severe, hyperinflammatory syndrome that can originate from diverse etiologies, often requiring critical care level management. Primary HLH, initially described in the 1940s, derives from genetic defects that result in uncontrolled immune activation. Although chemotherapy and immunosuppressive agents can temporarily quell inflammation, allogeneic hematopoietic cell transplantation (HCT) is the only curative option. In 2025, HCT is indicated for primary HLH and some etiologies of secondary HLH but remains challenging due to both disease and transplant-related inflammation. Additionally, new cellular therapy approaches to treat malignancy, such as chimeric antigen receptor T cells, can trigger a spectrum of hyperinflammatory complications. Herein, we review the pathophysiology, diagnosis, and evolving management approaches of primary and secondary HLH, ultimately informing our management of hyperinflammation in the setting of new cell therapies.